2D-FEA Based Design and Performance Analysis of Low Weight Segmented Rotor HE-FSM for Light Weight Aircrafts - Ali, Hassan; Sulaiman, Erwan; Omar, Zamri; F. Omar, M; Amin, Faisal (International Journal of Engineering and Technology, 2018)
All electric aircraft (AEA), is one of the main intentions of the aerospace industry for future. Where electrical machines are capable to provide high torque density and are dominant for the feasibility of direct drive electrical driving force for aircraft applications. Besides, low weight and high torque capabilities, the best candidate solution should also inherently fault tolerant for aircraft applications. For these reasons, a new sort of machine has been familiarized and published in last decade know as flux switching machine (FSM). FSMs contain all excitation sources on stator side with robust rotor structure. According to the type of excitation, FSMs are characterized into three types such as permanent magnet PM FSM, field excitation FE FSM and hybrid excitation HE FSM. PM FSM and FE FSM use PM and FE coil for their excitation sources respectively, whereas both PM and FE coil is used in HE-FSM for excitation. Subsequently, these machines have shown high torque to weight ratios and high efficiency during research in the last decade. Therefore in this paper, a new structure of 12S-8P HE-FSM with segmental rotor has been proposed and analyzed. The proposed segmented HE-FSM has the simple structure using only three PMs and three FECs. The proposed structure is analyzed using commercial 2D FEA package, JMAG-designer ver. 14.0. This paper presents the coil test analysis of segmented HE-FSM to confirm the working principle. Besides, cogging torque, flux strengthening, torque vs current densities and power vs current densities have been analyzed and presented.Â